Transferência do aprendido em cursos de especialização em gestão - Silva, Patrícia Teixeira Maggi da (2019)
Investments in different types of formal learning, which include training, courses, educational programs, among others, have been growing in Brazil and in other countries. This fact suggests that organizations evaluate formal learning positively. However, studies have shown controversial results regarding the real benefits of formal learning for organizations. These results may be partly explained by the difficulties in isolating the effects of formal learning from other factors. By investing in formal learning, organizations need to assess whether individuals are transferring what they have learned through behavioral changes at work. However, they don’t know how to do so, leading to the problem or gap of learning transfer, which is defined as the application or use at work of knowledge and skills acquired in different types of formal learning. From an academic perspective, studies of learning transfer advanced from the model and concept proposed by Baldwin and Ford (1988). Despite the increase in learning transfer research in the last decades, which proves its theoretical and practical importance, the literature still has some gaps: (1) the definition and operationalization of the construct learning transfer and its differentiation between use and effectiveness; and (2) the scarcity of research in long-term educational programs offered by higher education institutions. The present thesis aims to fill these two gaps. For the first one, it was developed a multidimensional learning transfer measure based on taxonomy of use proposed by Yelon, Ford and Bhatia (2014). For the second gap, the object of investigation was postgraduation management courses. This thesis aimed to: “Propose and test a learning transfer model in postgraduation management courses, assessing the simultaneous influence of organizational cynicism, critical reflection, transfer design, job autonomy and learning culture on the transfer of learning. To achieve this goal, the empirical research was carried out with students and graduates of postgraduation management courses including the MBA degree of higher education institutions in São Paulo. A final sample of 424 valid answers was obtained. For measuring the independent variables five measures were used: transfer design, critical reflection, organizational cynicism, job autonomy and learning culture. For the dependent variable learning transfer as use, a new scale was developed. Data were submitted to descriptive statistical analysis and multivariate techniques (correlations, confirmatory factor analysis, and structural equation modeling for hypothesis testing). The results confirmed three of the five hypotheses that predicted direct relationships with the dependent variable: critical reflection, transfer design and learning culture. They, respectively, explained 18%, 17% and 5% of the variation on learning transfer. The conceptual model also included the assessment of the moderating effects of organizational cynicism, job autonomy, and learning culture. These moderating effects haven’t been confirmed. Finally, the model included 15 control variables and only two of them had statistically significant results, but with small effects on learning transfer: age and management position.